A Monosaccharide Residue Is Sufficient to Maintain Mouse and Human IgG Subclass Activity and Directs IgG Effector Functions to Cellular Fc Receptors. - Kao, Daniela; Danzer, Heike; Collin, Mattias; Groß, Andrea; Eichler, Jutta; Stambuk, Jerko; Lauc, Gordan; Lux, Anja; Nimmerjahn, Falk (Cell Reports, 2015)
Immunoglobulin G (IgG) glycosylation modulates antibody activity and represents a major source of heterogeneity within antibody preparations. Depending on their glycosylation pattern, individual IgG glycovariants present in recombinant antibody preparations may trigger effects ranging from enhanced pro-inflammatory activity to increased anti-inflammatory activity. In contrast, reduction of IgG glycosylation beyond the central mannose core is generally believed to result in impaired IgG activity. However, this study reveals that a mono- or disaccharide structure consisting of one N-acetylglucosamine with or without a branching fucose residue is sufficient to retain the activity of the most active human and mouse IgG subclasses in vivo and further directs antibody activity to cellular Fcγ receptors. Notably, the activity of minimally glycosylated antibodies is not predicted by in vitro assays based on a monomeric antibody-Fcγ-receptor interaction analysis, whereas in vitro assay systems using immune complexes are more suitable to predict IgG activity in vivo.

IgG subclass and vaccination stimulus determine changes in antigen specific antibody glycosylation in mice - Kao, Daniela; Lux, Anja; Schaffert, Anja; Lang, Roland; Altmann, Friedrich; Nimmerjahn, Falk (European Journal of Immunology, 2017)
Immunoglobulin G (IgG) glycosylation can modulate antibody effector functions. Depending on the precise composition of the sugar moiety attached to individual IgG glycovariants either pro- or anti-inflammatory effector pathways can be initiated via differential binding to type I or type II Fc-receptors. However, an in depth understanding of how individual IgG subclasses are glycosylated during the steady state and how their glycosylation pattern changes during vaccination is missing. To monitor IgG subclass glycosylation during the steady state and upon vaccination of mice with different T-cell dependent and independent antigens, tryptic digests of serum, and antigen-specific IgG preparations were analyzed by reversed phase-liquid chromatography-mass spectrometry. We show that there is a remarkable difference with respect to how individual IgG subclasses are glycosylated during the steady state. More importantly, upon T-cell dependent and independent vaccinations, individual antigen-specific IgG subclasses reacted differently with respect to changes in individual glycoforms, suggesting that the IgG subclass itself is a major determinant of restricting or allowing alterations in specific IgG glycovariants.
EVALuna2:7735

Immune Monitoring of Trans-endothelial Transport by Kidney-Resident Macrophages - Stamatiades, Efstathios G.; Tremblay, Marie-Eve; Bohm, Mathieu; Crozet, Lucile; Bisht, Kanchan; Kao, Daniela; Coelho, Carolina; Fan, Xiying; Yewdell, William T.; Davidson, Anne; Heeger, Peter S.; Diebold, Sandra; et al. (Cell, 2016)
Small immune complexes cause type III hypersensitivity reactions that frequently result in tissue injury. The responsible mechanisms, however, remain unclear and differ depending on target organs. Here, we identify a kidney-specific anatomical and functional unit, formed by resident macrophages and peritubular capillary endothelial cells, which monitors the transport of proteins and particles ranging from 20 to 700 kDa or 10 to 200 nm into the kidney interstitium. Kidney-resident macrophages detect and scavenge circulating immune complexes "pumped'' into the interstitium via trans-endothelial transport and trigger a Fc gamma RIV-dependent inflammatory response and the recruitment of monocytes and neutrophils. In addition, Fc gamma RIV and TLR pathways synergistically "super-activate'' kidney macrophages when immune complexes contain a nucleic acid. These data identify a physiological function of tissue-resident kidney macrophages and a basic mechanism by which they initiate the inflammatory response to small immune complexes in the kidney.

Sweet and sour: the role of glycosylation for the anti-inflammatory activity of immunoglobulin G. - Kao, Daniela; Böhm, Sybille; Nimmerjahn, Falk (Current Topics in Microbiology and Immunology, 2014)
The importance of immunoglobulin G (IgG) molecules for providing long-term sterile immunity as well as their major contribution to tissue inflammation during autoimmune diseases is generally accepted. In a similar manner, studies over the last years have elucidated many details of the molecular and cellular pathways underlying this protective activity in vivo, emphasizing the role of cellular recognizing the constant antibody fragment. In contrast, the active anti-inflammatory activity of IgG, despite being known and actually identified in human autoimmune patients more than 30 years ago, is much less defined. Recent evidence from several independent model systems suggests that IgG glycosylation is critical for the immunomodulatory activity of IgG and that both monomeric IgG as well as IgG immune complexes can diminish Fc receptor and complement dependent inflammatory processes. Moreover, there is increasing evidence that IgG molecules also modulate B and T cell responses, which may suggest that IgG is centrally involved in the establishment and maintenance of immune homeostasis.

Targeting B cells and autoantibodies in the therapy of autoimmune diseases. - Kao, Daniela; Lux, Anja; Schwab, Inessa; Nimmerjahn, Falk (Seminars in Immunopathology, 2014)
B cells and B cell-derived autoantibodies play a central role in the pathogenesis of many autoimmune diseases. Thus, depletion of B cells via monoclonal antibodies such as Rituximab is an obvious therapeutic intervention and has been used successfully in many instances. More recently, novel therapeutic options targeting either the autoantibody itself or resetting the threshold for B cell activation have become available and show promising immunomodulatory and anti-inflammatory effects in a variety of animal models. The aim of this review is to summarize these results and to provide an insight into the underlying molecular and cellular pathways of these novel therapeutic interventions targeting autoantibodies and B cells and to discuss their value for human therapy.